Fables of Field and Staff - Frye, James A. (James Albert), 1863-1933 (Salt Lake City, UT : Project Gutenberg, 2015)
"Fables of Field and Staff" by James A. Frye is a collection of whimsical fables likely written in the late 19th century. The book details the amusing and sometimes outrageous experiences of a volunteer infantry regiment during peacetime, bringing to life the camaraderie and peculiarities of military life. Through its narratives, it explores a series of events surrounding the characters within the regiment, including various officers and a veteran named Sam, who often serves as a storyteller. At the start of the book, the tone is set with a preface that hints at the jests and camaraderie intrinsic to military culture. As the narrative unfolds, we are introduced to the mundane yet humorous atmosphere of the regiment, where a solitary and sleepy room serves as the backdrop for conversations among officers. One officer, Bones, recounts an amusing tale involving a previous captain named Merrowbank, whose misguided belief in the divine protection of his regiment led to a comical inspection debacle, ultimately resulting in the company being mockingly referred to as "The Forty Thieves." This blend of humor, military life anecdotes, and unique characters invites readers to indulge in the light-hearted exploration of life within the ranks. (This is an automatically generated summary.)
The march of the forty thieves -- A tale of two towers -- One from the veteran -- Woodleigh, Q.M. -- The Kerwick Cup -- Officially reported -- Special orders, no. 49.
Release date is 2015-03-21
E-text prepared by Charlie Howard and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Short stories, American; Soldiers -- Fiction